"God put weed here for us to smoke": A mixed-methods study of religion and spirituality among adolescents with cannabis use disorders. Issue 4 (2nd October 2018) - Yeterian, Julie D.; Bursik, Krisanne; Kelly, John F.
Abstract: Background: A growing literature on adults with substance use disorders (SUDs) suggests that religious and spiritual processes can support recovery, such that higher levels of religiosity and/or spirituality predict better substance use outcomes. However, studies of the role of religion and spirituality in adolescent SUD treatment response have produced mixed findings, and religiosity and spirituality have rarely been examined separately. Methods: The present study examined religiosity and spirituality as predictors of outcomes in an outpatient treatment adolescent sample ( N  = 101) in which cannabis was the predominant drug of choice. Qualitative data were used to contextualize the quantitative findings. Results: Results showed that higher levels of spirituality at posttreatment predicted increased cannabis use at 6-month follow-up (β = .237, p  = .043), whereas higher levels of baseline spirituality predicted a lower likelihood of heavy drinking at posttreatment (odds ratio [OR] = .316, P  = .040). Religiosity did not predict substance use outcomes at later time points. When asked to describe the relation between their religious/spiritual views and their substance use, adolescents described believing that they had a choice about their substance use and were in control of it, feeling more spiritual when under the influence of cannabis, and being helped by substance use. Conclusions: Together, findings suggest that for adolescents with SUDs, religion and spirituality may not counteract the use of cannabis, which may be explained by adolescents' views of their substance use as being consistent with their spirituality and under their control.